2012
DOI: 10.1111/j.1464-0597.2012.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Work–Family Enrichment among Chinese Employees: The Mediating Role between Work Support and Job Satisfaction

Abstract: This study adopted social exchange theory to investigate whether work‐to‐family enrichment functioned as a mediator between work support (supervisor support, co‐worker support, and organisational support) and job satisfaction among 543 employees in two cities in China. A series of confirmatory factor analyses (CFA) supported a 10‐item Work Support Scale measuring supervisor support, co‐worker support, and organisational support. Structural equation modelling (SEM) results showed that work‐to‐family enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 51 publications
(100 reference statements)
14
103
0
4
Order By: Relevance
“…From the perspective of COR theory, individuals with greater support from sources within the work domain are more capable of solving work-related problems and more likely to avoid problematic situations (Hobfoll 2002), allowing them to invest more resources in other life domains. Support from supervisors may provide the energy and psychological resource base needed to meet family-related responsibilities (Tang, Siu, and Cheung 2014), which may enhance quality of life in the family domain. Accordingly, Grzywacz and Marks (2000) reported that supervisor support was associated with greater positive spillover from work to family.…”
Section: Social Support and Work-family Enrichmentmentioning
confidence: 99%
“…From the perspective of COR theory, individuals with greater support from sources within the work domain are more capable of solving work-related problems and more likely to avoid problematic situations (Hobfoll 2002), allowing them to invest more resources in other life domains. Support from supervisors may provide the energy and psychological resource base needed to meet family-related responsibilities (Tang, Siu, and Cheung 2014), which may enhance quality of life in the family domain. Accordingly, Grzywacz and Marks (2000) reported that supervisor support was associated with greater positive spillover from work to family.…”
Section: Social Support and Work-family Enrichmentmentioning
confidence: 99%
“…These studies mainly examined gender as a moderator of the relationships between antecedents (e.g. social support at work, job characteristics) and WFE or WFE and attitudinal outcomes, such as job/family satisfaction, commitment and turnover intentions (Baral and Bhargava, 2011;Chen et al, 2016;Marques et al, 2015;Shockley and Singla, 2011;Tang et al, 2014). Only Baral and Bhargava (2011) tested differences in mean levels of WFE and found no significant gender differences for both directions of WFE.…”
Section: Work-family Enrichment and Gendermentioning
confidence: 99%
“…In contrast, men may feel less dissatisfi ed with their work even under high levels of WIF, because WIF does not endanger the accomplishment of their more salient work roles. Tang et al ( 2014 ) investigated whether workto-family enrichment functioned as a mediator between three types of work support (i.e., supervisor, co-worker, and organizational support) and job satisfaction among 543 employees in China. Results showed that work-to-family enrichment fully mediated the association of supervisor support and organizational support with job satisfaction.…”
Section: Work-family Interfacementioning
confidence: 99%